2018
DOI: 10.3389/fmicb.2018.01765
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomic Analysis of Streptococcus thermophilus TH1436 and TH1477 Showing Different Capability in the Use of Galactose

Abstract: Streptococcus thermophilus is a species widely used in the dairy industry for its capability to rapidly ferment lactose and lower the pH. The capability to use galactose produced from lactose hydrolysis is strain dependent and most of commercial S. thermophilus strains are galactose-negative (Gal−), although galactose-positive (Gal+) would be more technologically advantageous because this feature could provide additional metabolic products and prevent galactose accumulation in foods. In this study, a next gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 73 publications
(95 reference statements)
0
15
0
Order By: Relevance
“…The S. thermophilus strains were in the de Man, Rogosa, and Sharpe (MRS)-lactose broth with 2% lactose as the sole carbon source and were incubated at 37°C for 12 h under aerobic conditions before the analysis. After washing with a saline solution, the bacteria were transferred into the fresh MRS-lactose medium to an initial concentration of 5 × 10 6 cells/mL to record their growth, acid production, and rate of lactose utilization during incubation at 37°C for 16 h under aerobic conditions (Giaretta et al, 2018;Yang et al, 2019). After 12 h of incubation, the urease and β-galactosidase activities of the strains were determined as previously described, with 1 unit of urease activity defined as the release of 1 µmol of NH4 + per min (Mora et al, 2005;Zotta et al, 2008;Wu and Shah, 2017).…”
Section: Short Communication: Lactose Utilization Of Streptococcus Thmentioning
confidence: 99%
“…The S. thermophilus strains were in the de Man, Rogosa, and Sharpe (MRS)-lactose broth with 2% lactose as the sole carbon source and were incubated at 37°C for 12 h under aerobic conditions before the analysis. After washing with a saline solution, the bacteria were transferred into the fresh MRS-lactose medium to an initial concentration of 5 × 10 6 cells/mL to record their growth, acid production, and rate of lactose utilization during incubation at 37°C for 16 h under aerobic conditions (Giaretta et al, 2018;Yang et al, 2019). After 12 h of incubation, the urease and β-galactosidase activities of the strains were determined as previously described, with 1 unit of urease activity defined as the release of 1 µmol of NH4 + per min (Mora et al, 2005;Zotta et al, 2008;Wu and Shah, 2017).…”
Section: Short Communication: Lactose Utilization Of Streptococcus Thmentioning
confidence: 99%
“…Recently, Xiong et al (2019b) demonstrated that the Gal + phenotype of S. thermophilus depends upon the expression of the gal operon, which can be widely affected by a single point mutation at the -9 box in the galK promoter. Since the accumulation of galactose in the medium by S. thermophilus may be important from a technological or nutritional perspective (Giaretta et al, 2018), we examined the presence of the mutation at the -9 box in the galK promoter in the strains analyzed. Accordingly, only B59671, CS8, EPS, and NCTC12958 T seem to be able to catabolize galactose, as they own the relevant G to A mutation in the position -9 of the -10 box related Gal + phenotype (data not shown).…”
Section: Lactose and Galactose Metabolismmentioning
confidence: 99%
“…This suggests that this single point mutation of the galK promoter may largely be responsible for the Gal + phenotype of S-3. Giaretta et al (2018) also compared the gal promoters of Gal + and Gal − strains and found mutations at various positions in the gal operon intergenic regions. These mutations result in insufficient expression of the gal operon genes in the Gal − strains.…”
Section: Sugar Uptake In Eps Biosynthesis Based On Genome Analysis Of S Thermophilus S-3mentioning
confidence: 99%